Inspecting leadership styles and its impact on volunteers motivational in light of self-determination theory; case of Palestinian organizations in the health sector - Abed, Baraa (Technium Business and Management, 2025)
Motivating volunteers is one of the most prominent challenges facing organizations and countries, and this study aims to contribute to the scientific literature on the impact of different leadership styles on volunteer motivation based on the Self-Determination Theory of Motivation (SDT). Our study model, which was tested on 101 volunteers in the Palestinian health sector, showed the positive impact of inspirational motivation (IM), intellectual stimulation (IS), and individual consideration (IC) components on transformational leadership. The two dimensions of transactional leadership were positively related to intrinsic motivation (Int-M), introspective organization (INTRO), and external social organization (EXT-S). Meanwhile, the non-interventionist leadership dimension negatively affects introspective organization (INTRO) motivation. Our analysis of the elements of each leadership style and studying its impact on motivation provides insights for leaders in organizations that rely primarily on volunteers in their work. The study has important theoretical and practical implications.